10: INTRATHORACIC VERSUS CERVICAL ANASTOMOSIS AFTER MINIMALLY INVASIVE OESOPHAGECTOMY FOR OESOPHAGEAL CANCER: A RANDOMISED CONTROLLED TRIAL. (23rd April 2022) - Van Workum, F; Verstegen, M; Klarenbeek, B; Bouwense, S; Van Berge Henegouwen, M; Daams, F; Gisbertz, S; Hannink, G; Haveman, J W; Heisterkamp, J; Jansen, W; Kouwenhoven, E; et al.
Abstract: Background and aim: Transthoracic minimally invasive oesophagectomy (MIO) is increasingly performed as part of curative multimodality treatment. There is no robust evidence on the preferred location of the anastomosis after transthoracic MIO. The aim of this study was to compare an intrathoracic with a cervical anastomosis in a randomised controlled trial. Methods: An open multicentre randomised controlled superiority trial was performed. Patients with mid to distal oesophageal or gastro-oesophageal junction cancer planned for curative resection were included. Patients were randomly assigned (1:1) to transthoracic MIO with intrathoracic or cervical anastomosis. The primary endpoint was anastomotic leakage requiring endoscopic, radiologic or surgical intervention. Secondary outcomes were overall anastomotic leak rate, other postoperative complications, length of stay, mortality and quality of life. The ICAN trial is registered in the Dutch trial register under number NTR4333. Results: Two hundred and sixty-two patients were randomised and 245 were eligible for analysis. Anastomotic leakage necessitating re-intervention occurred in 15 of 122 (12.3%) patients with intrathoracic anastomosis and in 39 of 123 (31.7%) patients with cervical anastomosis (risk difference − 19.4%, 95% CI -29.5%—-9.3%). Overall anastomotic leak rate was 12.3% in the intrathoracic anastomosis group and 34.1% in the cervical anastomosis group (risk difference − 21.9%, 95% CI -32.1%—-11.6%). ICU length of stay, mortality rates and overall quality of life were comparable between groups, but intrathoracic anastomosis was associated with less severe complications, lower incidence of recurrent laryngeal nerve palsy and better quality of life in three subdomains. Conclusion: Intrathoracic anastomosis is the preferred technique for patients treated with transthoracic MIO for mid to distal oesophageal or gastro-oesophageal junction cancer.